SIKUAD Management In Improving School Performance at SMK Negeri 2 Purwodadi - Eka Wulandari; Nurkolis; Br Ginting, Rosalina (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
This study examines the management of SIKUAD (Academic Information System) in improving school performance at SMK Negeri 2 Purwodadi. The study is grounded in the premise that the effectiveness of an academic information system depends not only on technological features but also on the quality of managerial processes supporting its implementation. This research aims to analyze the management of SIKUAD based on four management functions, planning, organizing, actuating, and controlling, and to identify its direct implications for school performance improvement. A qualitative case study design was employed. The research was conducted from December to February and involved one principal, one vice principal for curriculum, two system operators, five teachers, and three students selected purposively. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using interactive data analysis supported by triangulation and member checking. The findings indicate that systematic planning through needs analysis and policy formulation ensured initial readiness and minimized administrative errors. Clear organizational structuring facilitated coordination between management, operators, and teachers. The consistent implementation of the system significantly accelerated grade processing, reduced reporting delays, improved real-time monitoring of learning activities, and decreased administrative complaints. Continuous monitoring and evaluation strengthened teacher discipline, data accuracy, and institutional accountability. The study concludes that well-managed SIKUAD contributes directly to administrative efficiency, transparency, and overall school performance improvement.